2021
DOI: 10.1038/s41423-021-00742-4
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Tregs in cancer metastasis: opportunities for precision immunotherapy

Abstract: Decades of advancements in immuno-oncology have enabled the development of current immunotherapies, which provide long-term treatment responses in certain metastatic cancer patients. However, cures remain infrequent, and most patients ultimately succumb to treatment-refractory metastatic disease. Recent insights suggest that tumors at certain organ sites exhibit distinctive response patterns to immunotherapy and can even reduce antitumor immunity within anatomically distant tumors, suggesting the activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 190 publications
(158 reference statements)
2
41
0
1
Order By: Relevance
“…In the tumor microenvironment, T cells had complex functions due to their different subtypes. Regulatory T cells (Tregs) could attenuate effector T cell activity and promote immunosuppression ( Najafi and Mirshafiey, 2019 ; Huppert et al, 2022 ). CD8 + T cells have been considered as a positive prognostic biological maker because of its cytotoxic and tumor-killing capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, T cells had complex functions due to their different subtypes. Regulatory T cells (Tregs) could attenuate effector T cell activity and promote immunosuppression ( Najafi and Mirshafiey, 2019 ; Huppert et al, 2022 ). CD8 + T cells have been considered as a positive prognostic biological maker because of its cytotoxic and tumor-killing capabilities.…”
Section: Discussionmentioning
confidence: 99%
“… 60 Tregs promote cancer cell invasion by affecting the EMT status. 61 , 62 In addition, Tregs promote tumour angiogenesis in the TME through the secretion of VEGF‐A and IL‐10, thereby supporting tumour metastasis. 63 In vivo experiments, the tumour volume was significantly smaller after eliminating Tregs with anti‐IL‐10 or anti‐CD25, which confirmed the effect of Tregs on tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour‐infiltrating Tregs inhibit anti‐tumour immune response via several pathways, including the production of immunosuppressive cytokines, PD‐1 checkpoint inhibition and up‐regulation membrane protein PD‐1 and CTLA‐4, 58,59 ultimately facilitating tumour metastasis 60 . Tregs promote cancer cell invasion by affecting the EMT status 61,62 . In addition, Tregs promote tumour angiogenesis in the TME through the secretion of VEGF‐A and IL‐10, thereby supporting tumour metastasis 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Tregs, a subgroup of CD4 + helper T cells identified by CD25 and Foxp3 expression, play an immunosuppressive role in cancer. Tregs attenuate antitumor immunity by secreting immunosuppressive cytokines, interfering with tumor-associated antigen presentation, and inhibiting cytotoxic cell function ( 38 , 39 ). It has been demonstrated that Foxp3 expression in ESCC means a poor prognosis ( 40 , 41 ).…”
Section: The Role Of Tumor Microenvironment In Esophageal Squamous Ce...mentioning
confidence: 99%